CoO doping effects on the ZnO films through EBPDV technique - Basso Bernardi, Maria Ines; Queiroz Maia, Lauro June; Antonelli, Eduardo; Mesquita, Alexandre [UNESP]; Li, Maximo Siu; Gama, Lucianna (Edp Sciences S A, 2014)
Nanometric Zn1-xCoxO ( x = 0.020, 0.025 and 0.030 in mol.%) nanopowders were obtained from low temperature calcination of a resin prepared using the Pechini's method. Firing the Zn1-xCoxO resin at 400 degrees C/2 h a powder with hexagonal structure was obtained as measured by X-ray diffraction (XRD). The powder presented average particle size of 40 nm observed by field emission scanning electronic microscopy (FE-SEM) micrographs and average crystallite size of 10 nm calculated from the XRD using Scherrer's equation. Nanocrystalline Zn1-xCoxO films with good homogeneity and optical quality were obtained with 280-980 nm thicknesses by electron beam physical vapour deposition (EBPVD) under vacuum onto silica substrate at 25 degrees C. Scanning electron microscopy with field emission gun showed that the film microstructure is composed by spherical grains and some needles. In these conditions of deposition the films presented only hexagonal phase observed by XRD. The UV-visible-NIR and diffuse reflectance properties of the films were measured and the electric properties were calculated using the reflectance and transmittance spectra.